Knowledge and awareness about herpes labialis among dental clinical students: a survey - Bansal, Anshul; Arora, Divya; Bansal, Parul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Herpes virus (HSV) is a worldwide healthcare problem. Dental health care professionals are at a high risk of infection by HSV. The present study investigated the knowledge and awareness of HSV infection among dental Interns in dental colleges. Methods: This was a questionnaire-based cross-sectional study. A self-administered questionnaire consisting of questions on students’ knowledge and awareness regarding HSV was used. Data of 126 participants were analysed using SPSS (Statistical Package for Social Studies) version 22.0. Results: Overall, the participants showed only a fair level of knowledge about HSV. As the respondents of the study were clinical dental students, it was expected to have a high level of awareness. Conclusions: These unsatisfactory findings emphasize the necessity of continued education about HSV in order to improve knowledge and awareness of dental students regarding HSV.